Trends in hospital admissions for adrenal insufficiency in adolescents and young adults in the 21st century - Chrisp, Georgina L.; Quartararo, Maria; Torpy, David J.; Falhammar, Henrik; Rushworth, R. Louise (Frontiers in Endocrinology, 2022)
Background Very little is known about the epidemiology of adrenal crises (AC) and adrenal insufficiency (AI) in adolescents and young adults. Methods Data on all admissions to Australian hospitals between 2000/1 to 2019/20 for a principal diagnosis of AI (including AC) in 10-24 year olds were extracted from a national repository. Age and sex-specific rates and age-adjusted rates were compared. Findings Over the study, there were 3386 admissions for a principal diagnosis of AI; 24.0% (n=812) were for an AC and 50·7% (n=1718) were for secondary AI. Age-adjusted AI admissions increased from 31·70/million in 2000/1 to 54·68/million in 2019/20 (p<0·0001). Age-adjusted AC admissions also increased, most notably in the second decade (from 5·80/million in 2010/11 to 15·75/million in 2019/20) (p<0·00001). Average AI and AC admission rates were comparable between the sexes, but rates increased significantly in females, especially in those aged 20 to 24 years, whose AC rate in 2019/20 (39·65/million) was significantly higher than the corresponding rate in 2000/1 (3·15/million) (p<0·00001). Average age-adjusted SAI admission rates were higher in males (23·92/million) than females (15·47/million) (p<0·00001). However, SAI admission rates increased only among females (from 11·81/million to 22·12/million in 2019/20), with an increase in 20-24 year old females in the second decade from 5·07/million in 2010 to 20·42/million (p<0·00001). Age adjusted admissions for congenital adrenal hyperplasia, primary AI (PAI) and drug-induced AI did not change significantly over the study. Interpretation AC/AI admissions increased over the first two decades of this century in the emerging adult population, particularly among females who also experienced a marked increase in AC admission rates, most evident in the second decade. Although uncertain, possible explanations include: dose of glucocorticoid replacement; non-adherence to therapy; psychosocial factors; and difficulty in transition to adult services. Admissions for SAI also increased, while rates of PAI and CAH remained constant.